Immune Checkpoint Inhibitors for Vaccine Improvements: Current Status and New Approaches - Alexander Batista-Duharte; Fakhri Hassouneh; Pablo Alvarez-Heredia; Alejandra Pera; Rafael Solana (Pharmaceutics, 2022)
In recent years, the use of immune checkpoint inhibitors (ICIs) in combination with approved or experimental vaccines has proven to be a promising approach to improve vaccine immunogenicity and efficacy. This strategy seeks to overcome the immunosuppressive mechanisms associated with the vaccine response, thereby achieving increased immunogenicity and efficacy. Most of the information on the use of ICIs combined with vaccines derives from studies on certain anti-tumor vaccines combined with monoclonal antibodies (mAbs) against either cytotoxic T lymphocyte-associated protein 4 (CTLA-4), programmed cell death protein 1 (PD-1), or programmed death-ligand 1 (PD-L1). However, over the past few years, emerging strategies to use new-generation ICIs as molecular adjuvants are paving the way for future advances in vaccine research. Here, we review the current state and future directions of the use of ICIs in experimental and clinical settings, including mAbs and alternative new approaches using antisense oligonucleotides (ASOs), small non-coding RNAs, aptamers, peptides, and other small molecules for improving vaccine efficacy. The scope of this review mainly includes the use of ICIs in therapeutic antitumor vaccines, although recent research on anti-infective vaccines will also be addressed.